FAKTOR PENENTU EFEKTIVITAS PENGELOLAAN KEUANGAN BADAN LAYANAN UMUM UNIVERSITAS BENGKULU - Verawati, Hasrini; Husaini, Husaini; Aisyah, Siti (UNIB Press, 2016)
This study aims to examine and obtain empirical evidence about the factors that influence the effectiveness of financial management. The variables to be tested in this study of human resources, the utilization of information technology, systems of internal control, and governance of the effectiveness of financial management.This research was conducted by giving questionnaires to financial managers the University of Bengkulu that have been based on the ease of obtaining the sample.The results of this study are quality human resources and internal control system does not affect the effectiveness of financial management. As for the utilization of research results and governance of information technology or a significant positive impact on the effectiveness of the financial management of public service agencies at the University of Bengkulu